Dance Arrangement Through Child Psycology - Lilik Subari (Terob : Jurnal Pengkajian dan Penciptaan Seni, 2023)
Art, especially dance as an expression of beauty is one of the universal human needs. It does not only belong to the rich and the all-sufficient, but also belong to everyone. When compared with the economy, art can be considered a luxury and is often seen as secondary need. However, in fact art can be found in every layer of society, human beings, whenever and wherever they live. Culture is always attached to human life, both individually and with the surrounding community. The art problem approach should be understood. It is impossible for people to talk about art without paying attention to the messages contained symbolically, in addition to the artistic activities themselves being the embodiment of the functions of certain cultural subsystems. As a dance teacher, the job is not only to provide dance material, but also to take responsibility for students’ behavior which has an impact on the development of learning in class and their psychological. There are a number of things that must be considered, including: the dance teacher must understand the purpose, content, function; the dance teacher must take into account the weight of the material to be taught; the dance teacher must take into account the psychological influence of children. Realizing all of these things, demands are not only on students to be able to understand teaching material but more than that.